Surface Modifying Substances that Reduce Apparent Yeast Cell Hydrophobicity. Issue 3 (2005) - Colling, Lisa; Essmann, Michael; Hollmer, Cara; Larsen, Bryan
Abstract : Objective. To determine whether several topical compounds and other chemical entities are able to diminish the surface hydrophobicity of yeast cells. Method. Hydrophobicity of yeast cells was determined by binding styrene microspheres to the surface of untreated yeast or yeast pre-incubated with various substances with potential for cell surface modification. The degree of microsphere adherence to yeast cells was measured by flow cytometry. Results. A significant reduction in cell surface hydrophobicity was observed when yeast was incubated in protein-containing media. Other compounds that effectively reduced microsphere binding were various formulations of K-Ymml ® and heparin. Divalent cations( Ca ++, Mg ++, Zn ++, Cu ++ ) were also potent inhibitors of microsphere adherence. It was possible to remove substances contributing to microsphere binding by chemical extraction of the yeast. Yeast having reduced microsphere binding activity also showed diminished binding of concanavalin A. Conclusions. Several commercially available compounds were able to block binding of styrene microspheres to yeast. Some of the binding activity appeared to be attributable to mannose-containing surface components. These findings have implications for formulating therapeutic products that might block yeast binding to tissues.